Horrible Harry and the dungeon - Kline, Suzy (Viking, 1996)
It's almost summer vacation and the students in room 2B are having trouble concentrating on their butterfly project, until a frightening-looking new teacher comes to supervise the Suspension Room and Harry is sent there as punishment for unruly behavior.